Utilizing Ulū al-Albāb Approach for Managing Organizational Knowledge Assets - Mhd. Sarif, Suhaimi; Ismail, Yusof (2012)
This paper postulates Ulū al-Albāb approach in managing organizational knowledge assets to achieve organizational sustainable innovation and competitive advantage. The knowledge-based view offers an integrative framework to achieve sustainable knowledge management and organizational learning that are driven by knowledge-based view of firm innovation. The KBV view lacks of spirituality foundation to sustain intellectual contribution from knowledge workers. An opinion survey with knowledge workers who are familiar with the conventional management of knowledge assets perceived that the Ulū al-Albāb approach is commendable insights into dynamism, uncertainty and complex business contexts. The current stage of the Ulū al-Albāb approach has yet to be operationalized to fit into the contemporary business models and processes. However, the views of the knowledge workers are not comprehensive and rigorous without the views from other stakeholders. Nevertheless, managers can utilize the Ulū al-Albāb approach into its communities of practice and social network in managing organizational knowledge assets. The Ulū al-Albāb approach contributes to the theoretical and practical understanding of managing organizational knowledge assets.